Cerliponase alfa changes the natural history of children with neuronal ceroid lipofuscinosis type 2: The first French cohort. (January 2021) - Estublier, Bastien; Cano, Aline; Hoebeke, Célia; Pichard, Samia; Scavarda, Didier; Desguerre, Isabelle; Auvin, Stéphane; Chabrol, Brigitte
Abstract: Introduction: Neuronal Ceroid Lipofuscinosis type 2 (CLN2) is a neurodegenerative lysosomal disease which leads to early dementia and death without treatment. The recently available therapy consists of intracerebroventricular enzyme substitution: cerliponase alfa. In this report, we describe the evolution of the first French children treated with cerliponase alfa. Method: CLN2 Clinical Rating Scale Motor-Language (CLN2 ML) assesses the motor and language evolution of CLN2 patients. We retrospectively studied patients' medical records: clinical symptoms, MRI conclusions, gene mutation, side effects of infusions, patient's age and CLN2 ML scores at diagnosis, at the beginning of enzyme replacement therapy (ERT) and at the last evaluation. Seven patients were included. Results: Average age at diagnosis was 50 months ( ±10) with CLN2 ML score equal to 3.6 [1.5–5]. Average age at the beginning of ERT was 56 months ( ±13) with CLN2 ML score equal to 3.1 [1–5]. At the last available evaluation, average age was 82 months ( ±20) with CLN2 ML score equal to 2.8 [0–5]. Thus, in 26 months, the mean CLN2 ML score only decreased by 0.3 points. However, patients with a CLN2 ML score greater than three at the onset of ERT experienced a stabilisation or improvement of clinical signs, whereas patients with a CLN2 ML score less than three at baseline continue to deteriorate. Conclusion: For patients starting ERT at an early stage of the disease, cerliponase alfa changes the natural history of the disease with a halt in disease progression or even a slight improvement in clinical symptoms. Highlights: Neuronal Ceroid Lipofuscinosis type 2 (CLN2) is a neurodegenerative disease. Speech delay, myoclonic epilepsy and gait disturbance must lead to a rapid diagnosis. Cerliponase alfa is an intracerebroventricular enzyme replacement therapy (ERT). Early initiation of ERT can stop evolution of the disease. ERT in patients with advanced stage of the disease does not prevent the worsening of the symptoms.